Perspectives on End-of-Life Treatment among Patients with COPD: A Multicenter, Cross-sectional Study in Japan. (2nd January 2019) - Fuseya, Yoshinori; Muro, Shigeo; Sato, Susumu; Sato, Atsuyasu; Tanimura, Kazuya; Hasegawa, Koichi; Uemasu, Kiyoshi; Hamakawa, Yoko; Takahashi, Yoshimitsu; Nakayama, Takeo; Sakai, Naoki; Fukui, Motonari; et al.
Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality. Since patients with severe COPD may experience exacerbations and eventually face mortality, advanced care planning (ACP) has been increasingly emphasized in the recent COPD guidelines. We conducted a multicenter, cross-sectional study to survey the current perspectives of Japanese COPD patients toward ACP. "High-risk" COPD patients and their attending physicians were consecutively recruited. The patients' family configurations, understanding of COPD pathophysiology, current end-of-life care communication with physicians and family members, and preferences for invasive life-sustaining treatments including mechanical ventilation (MV) and cardiopulmonary resuscitation (CPR) were evaluated using a custom-made, structured, self-administered questionnaire. Attending physicians were also interviewed, and we evaluated the patient–physician agreement. Among the 224 eligible "high-risk" patients, 162 participated. Half of the physicians (54.4%) thought they had communicated detailed information; however, only 19.4% of the COPD patients thought the physicians did so (κ score = 0.16). Less than 10% of patients wanted to receive invasive treatment (MV, 6.3% and CPR, 9.4%); interestingly, more than half marked their decision as "refer to the physician" (MV 42.5% and CPR 44.4%) or "refer to family" (MV, 13.8% and CPR, 14.4%). Patients with less knowledge of COPD were less likely to indicate that they had already made a decision. Although ACP is necessary to cope with severe COPD, Japanese "high-risk" COPD patients were unable to make a decision on their preferences for invasive treatments. Lack of disease knowledge and communication gaps between patients and physicians should be addressed as part of these patients' care.